2017
DOI: 10.1111/ajo.12695
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intravenous iron polymaltose, iron sucrose and ferric carboxymaltose in pregnancy: A systematic review

Abstract: Background: Intravenous (IV) iron in pregnancy is useful where oral iron is not tolerated or a rapid replenishment of iron is required. Aims:To review the literature on the efficacy and safety of different IV iron preparations in the management of antenatal iron-deficiency anaemia (IDA). Materials and methods:We searched MEDLINE, Embase and Scopus from inception to June 2016. Eligible studies were randomised controlled trials (RCTs) and observational studies, involving administration of IV iron (ferric carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 56 publications
(114 reference statements)
1
69
0
3
Order By: Relevance
“…Systematic reviews and meta‐analyses found that pregnant women receiving intravenous (IV) iron, compared with oral iron, achieved the target Hb more often, had an increased Hb after 4 weeks and had fewer side effects (Govindappagari & Burwick, ; Govindappagari & Burwick, ; Qassim et al , ).…”
Section: Management Of Iron Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic reviews and meta‐analyses found that pregnant women receiving intravenous (IV) iron, compared with oral iron, achieved the target Hb more often, had an increased Hb after 4 weeks and had fewer side effects (Govindappagari & Burwick, ; Govindappagari & Burwick, ; Qassim et al , ).…”
Section: Management Of Iron Deficiencymentioning
confidence: 99%
“…Systematic reviews and meta-analyses found that pregnant women receiving intravenous (IV) iron, compared with oral iron, achieved the target Hb more often, had an increased Hb after 4 weeks and had fewer side effects (Govindappagari & Burwick, 2018;Govindappagari & Burwick, 2019;Qassim et al, 2018). IV iron therapy is indicated when there is absolute noncompliance with, or intolerance of, oral iron therapy or proven malabsorption or when a rapid Hb response is required.…”
Section: Intravenous Iron Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of ANZJOG , Qassim and colleagues examine the use, safety and efficacy of IV iron polymaltose (IPM; Ferrosig®, Ferrum H®) in the management of iron deficiency in pregnancy . The findings of the current study, together with those of their ANZJOG 2017 systematic review of the safety and efficacy of three commonly used IV iron preparations in pregnancy, are timely and important. Data from the Australian Government Department of Health show that the number of women of reproductive age receiving IV iron more than doubled in Australia between 2014 and 2017 (M. Keaney, personal correspondence).…”
mentioning
confidence: 93%
“…It also showed that none of the preparations are superior to each other; hence iron sucrose has a clear advantage of being cheaper and readily available. 14 Dubey S et al, in a randomized trial used iron sucrose or oral iron in 200 pregnant patients and followed them up at 2,4 and then 4 weeklies till delivery. At all levels, it was shown that iron sucrose increased hemoglobin and iron stores faster than oral iron significantly (p-values of 0.000).…”
Section: Discussionmentioning
confidence: 99%